Quiescent Elongation of α-Synuclein Pre-form Fibrils Under Different Solution Conditions - Mao, Hengxu; Ye, Yongyi; Sun, Xiang; Qian, Chen; Wang, Baoyan; Xie, Linghai; Zhang, Shizhong (Frontiers in Neuroscience, 2022)
The intracellular aggregation of α-synuclein in neurons/glias is considered to be a key step in the pathogenesis of synucleinopathy (including PD, DLB, MSA, etc.). Increasing evidence indicates that the initial pathological α-synuclein aggregates can replicate themselves and propagate in a “seeding” manner to multiple areas of the brain and even to peripheral skin tissue, which makes it the most important biomarker for the diagnosis of synucleinopathies in recent years. The amplification and propagation capabilities of α-synuclein aggregates are very similar to those of prion-like diseases, which are based on the inherent self-recruitment capabilities of existing misfolded proteins. In vitro, by adding a small amount of pre-formed fibrils to the monomer solution, the recruitment process can be reproduced in a simplified model which may, to a certain extent, reveal part of the properties of α-synuclein aggregates. In this study, we explored the elongation rate of α-synuclein seeds under a quiescently incubating condition (rather than shaking/agitating). By using ThT fluorescence assay, we compared and quantified the elongation fluorescence curves to explore the factors that affect fibril elongation. These factors include proteins concentration, temperature, NaCl strength, SDS, temperature pretreatment and so on. Our work further describes the elongation of α-synuclein fibrils under quiescent incubation conditions. This may have important implications for the in vitro amplification and preservation of α-synuclein aggregates to further understand the prion-like transmission mechanism of PD.